Bilingüismo e code-switching: um estudo de caso - Cristino, Luciana dos Santos (2008)
This research aims at investigating the occurrence of code-switching in the speech of a late bilingual subject, under sociolinguistic and psycholinguistic perspectives. Code-switching or code alternation is a communicative strategy used by bilingual speakers in a given social situation. The word bilingual primarily describes someone who is proficient in two languages. This term can, however, also include the many people in the world who have varying degrees of proficiency in three, four or even more languages simultaneously (Wei, 2000) Adopting the parameters of qualitative research, we have done a case study of a 39-year-old Nigerian male bilingual who has lived in Brazil for about 6 years working as an English teacher and is married to a Brazilian. The data was collected by means of five different instruments: audio and video recording of an oral presentation of the subject to a group of students in a Brazilian school in a bilingual context (English/Portuguese), followed by an interview session; a closed individual interview recorded on audio tape, made by means of discrete questions; a written questionnaire in order to collect some personal data about the subject; a visual perception test to detect the preferential language in a free speech context; and an auto-confrontation or reflexive interview. Only the passages where the code-switching phenomenon occured were transcribed and analyzed. Some sentences of this corpus were selected for acoustic analysis and some charts of duration and F0 measures were made to analyze some prosody aspects of the native speaker when speaking the first language and the second language. The final results indicate that: (1) although the subject prefers the mother tongue (English), code-switching occurs in both ways: first language second language / second language first-tongue language; (2) the data analyses suggest that the subject uses different strategies for choosing lexical items, according to the context, the interlocutor, and the place, and that the change of the linguistic code appears most of the time initiated by the OK interjection. The emotional aspect is also worth mentioning: the subject is always worried about the interlocutor and wants to know whether he has made himself clear. The pronunciation of Portuguese words are heavily influenced by his first language; (3) we could observe, from the acoustic analyses , that the intonation curve of the yes/no questions produced in English bears much resemblance to English melodic patterning in that the subject keeps the the intonational aspects of the matrix language; (4) there is considerable alteration in the fonotaxe of some words used by the speaker; (5) the altered lexical item is replaced by words belonging to the same syntactic level